IMPLEMENTASI INTEGRATED MARKETING COMMUNICATION GUNAWANGSA HOTEL MANYAR SURABAYA DALAM UPAYA MENINGKATKAN MINAT KONSUMEN - Prayagati, Rosa Petrinevanti Rasendriya; Setianingrum, Vinda Maya (The Commercium, 2025)
Surabaya as a city of business and tourism makes this city has a variety of hotels to meet the needs of the community. Gunawangsa Hotel Manyar Surabaya as one of the three-star hotels that exist in the city of Surabaya undertakes promotional efforts so that the public has an interest in making Gunavangsa Hotel Manyar Surabaya as an option for them both to stay or organize events. This research aims to find out how the implementation of integrated marketing communication carried out by Gunawangsa Hotel Manyar Surabaya in an effort to increase consumer interest. This research is qualitative research with the paradigm of constructivism, a paradigm that sees social conditions as a systematic analysis. The data collection was obtained from in-depth interviews with a number of informants that matched the criteria. The results of this study indicate that the mix of promotions on IMC applied by Gunawangsa Hotel Manyar Surabaya has six aspects including advertising: banners and brochures, events & experience activities live cooking, public relations & publicity i.e. making press releases, media visits, including PHMI, as well as CSR, personal selling activities sales calls, sales trip, telemarketing, and exhibitions, sales promotion giving discount prices, online & social media marketing doing promotion through instagram.